European Union dalam Hukum Internasional - Ariadno, Melda Kamil (UI Scholars Hub, 2005)
European Union has developed from just merely economic coooperation into much stronger bond among its Member States to include unified currency and common foreign security principle. Nevertheless the biggest challenge for European Union is its own status the intern ational law, whether it obtains status as an international legal person whilst eventually will enable it to play more influental role in international community such as the formation of international relation. This article will observe this issue by brought up the internal debates on European union status in international law.